Pelatihan Penerapan Etika Dalam Bermedia Sosial - Basuki Edi Priyo; Hemdani Rahendra Herlianto; Andriani (VIDHEAS: Jurnal Nasional Abdimas Multidisiplin, 2024)
The "Implementation of Ethics in Social Media" training held at the Alby wa Nur Foundation aims to improve participants' understanding of relevant ethical principles in interacting on social media platforms. This training is designed to address the challenges and risks associated with the use of social media, such as privacy, security, and negative social impacts. In this training, participants will learn about the importance of respecting the privacy of others, understanding the consequences of spreading inaccurate or detrimental information, and building a responsible and empathetic attitude in communicating online. The training materials will also cover best practices in managing online reputation and how to avoid behavior that can harm yourself or others. The training methods include presentations, interactive discussions, and case studies to facilitate a deep understanding and direct application of ethical principles in real situations. Thus, it is hoped that this training will equip participants with the skills needed to use social media responsibly, maintain healthy relationships online, and contribute positively to their digital environment. Keywords: Ethics, Morals, Interaction, Social Media